2020
DOI: 10.1371/journal.pone.0237523
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic and surgical therapies for patients with Meniere’s disease: A systematic review and network meta-analysis

Abstract: Background Meniere's disease (MD) is a chronic condition of the inner ear consisting of symptoms that include vertigo attacks, fluctuating sensorineural hearing loss, tinnitus and aural fullness. Despite availability of various interventions, there is uncertainty surrounding their relative efficacy, thus making it difficult to select the appropriate treatments for MD. The objective of this systematic review was to assess the relative effects of the available pharmacologic and surgical interventions in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
0
9
0
8
Order By: Relevance
“…Recently, the use of IT steroids has overtaken oral administration thanks to the absence of many undesirable side effects or contraindications; this observation is particularly of note when approaching an older MD patient in whom the risk of possible adverse effects such as infections, [81][82][83], the effect of IT steroid treatment in MD is questionable, especially in terms of vertigo control [84,85]. Despite the fact that a general consensus on MD therapy has not been reached, the use of IT gentamicin injections in patients with resistant forms has been accepted by most authors [86][87][88], while IT steroidal injections do not seem to be equally effective, at least in terms of vertigo control [88][89][90]. Gentamicin possesses toxic activity against the inner ear hair cells, especially against type 1 vestibular hair cells, and the aim of IT gentamicin is to obtain a long-lasting, non-fluctuating, peripheral vestibular hypofunction capable of being centrally compensated.…”
Section: Ménière's Disease (Md)mentioning
confidence: 99%
“…Recently, the use of IT steroids has overtaken oral administration thanks to the absence of many undesirable side effects or contraindications; this observation is particularly of note when approaching an older MD patient in whom the risk of possible adverse effects such as infections, [81][82][83], the effect of IT steroid treatment in MD is questionable, especially in terms of vertigo control [84,85]. Despite the fact that a general consensus on MD therapy has not been reached, the use of IT gentamicin injections in patients with resistant forms has been accepted by most authors [86][87][88], while IT steroidal injections do not seem to be equally effective, at least in terms of vertigo control [88][89][90]. Gentamicin possesses toxic activity against the inner ear hair cells, especially against type 1 vestibular hair cells, and the aim of IT gentamicin is to obtain a long-lasting, non-fluctuating, peripheral vestibular hypofunction capable of being centrally compensated.…”
Section: Ménière's Disease (Md)mentioning
confidence: 99%
“…However, due to the lack of comparison of clinical efficacy between different surgical methods, it is difficult to determine the optimal approach for refractory Menière's disease (16). Therefore, the aim of the present study is to evaluate the effectiveness of TSCO to control vertigo attacks over the long term and improve quality of life compared to traditional VNS.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the combination of intratympanic steroids and Gentamicin reduced the vestibular symptoms and protected the hearing. 16 Geng et al, treated 139 patients with intratympanic Gentamicin and Dexamethasone and studied the drug's effects in the case-control trial. They found that treated patients had a marked reduction in circulating IgG and IgM antibodies, tinnitus, vertigo, and instability decreased in the treated group compared to the age and gender-matched control group.…”
Section: Discussionmentioning
confidence: 99%